Education gap between second-generation migrants and natives and the role of intergenerational transmission of education: The French case. Issue 2 (2nd May 2017) - Fleury, Nicolas
Abstract : Purpose: The purpose of this paper is to analyse the role played by parental education endowments vs intergenerational transmission of education in education differences between second-generation immigrants and natives for the French case. Design/methodology/approach: First, estimates of human capital accumulation functions are performed by using a representative sample of the French population. Second, the Blinder-Oaxaca decomposition technique is implemented to underline the specific roles of differences in parental education endowments and of differences in intergenerational transmission in education between origins. Findings: The econometric estimates of human capital accumulation function parameters underline that the determinants of education level (and their magnitude), differ substantially between natives and migrants. They also underline evidence of heterogeneity in the intergenerational transmission of education among the different origins of migrants in France. The Oaxaca-Blinder decomposition results show that parental education endowments account differences for a significant part of the education gaps among origins. No evidence is found that differences in parental transmissions of education explain these gaps. Originality/value: The paper focusses on France, a country with a rich history of immigration in the twentieth century. The econometric analysis is based on a rich source of data for France that allows studying intergenerational mobility in education and also distinguishing natives from second-generation migrants based on their geographical origin.